A estrutura narrativa em séries de televisão americanas : NYPD Blue, The Sopranos e Braking Bad : as diferentes estratégias no desenvolvimento de histórias durante a virada do milênio - Silva, Anaurelino Negri da Costa (2017)
This dissertation aims to analyze North America television series developed over the last thirty years to understand its narrative structures and to check differences and similarities in how these programs develop their content over time. In order to do so, at first a literature review will be done to define the state of the art of other studies that have the same theme. Then methodological procedures will be used to select the ideal research object and to assist in the analysis of that content. To achieve that, this work uses the ideas of Arlindo Machado, Boris Tomachevski, Robert McKee and Steven Johnson as reference. It also analyzes the well-known TV shows NYPD Blue (1993 - 2005), The Sopranos (1999 - 2007) and Breaking Bad (2008 - 2013) and proposes another form of narrative analysis for television series.